Computer Hardware Troubleshooting System Using Expert System Shell - Zulkifli, Sarah Haryati (Universiti Teknologi Petronas, 2006)
The primary objective of this project is to develop a computer troubleshooting system that focuses on hardware problems. This system will be implemented using an expert system shell that is freely available on the Internet. E2gLite Expert System Shell was chosen to be used for this project because of the advantages it gives in terms of ease of use and time saved. It is also flexible and is easily integrated for use on the Internet. The main objective is to make the system easy to use and understandable by the users. Diagnosing hardware problems can be made easier if done in a systematic manner. This project hopes to give users the ability to gain knowledge and insight on how to diagnose and troubleshoot possible problems in the future.